Monetary Incentives Increase Metacognitive Confidence in Source Memory Performance in Patients With Schizophrenia - Szczepanowski, Remigiusz; Cichoń, Ewelina; Pasieczna, Aleksandra Helena; Gawęda, Łukasz; Rosińczuk, Joanna (Frontiers in Psychiatry, 2020)
Background Contemporary psychiatric research focuses its attention on the patient's dysfunction of metacognition in relation to the basic cognitive processes of mental activity. The current study investigated dysfunctional metacognition in relation to self-monitoring of memory in patients diagnosed with schizophrenia. Dysfunctions in metacognition were examined by focusing on two types of metacognitive measures: post-decision wagering scale (PDW) and confidence ratings scale (CR). Objectives The research employed an action-memory task that required patients with schizophrenia (N=39) and healthy controls (N=50) to evaluate their metacognition by categorizing self-monitoring actions (imagined vs. performed actions) either with post-decision wagering (PDW) or confidence ratings (CR). It was hypothesized that metacognition in self-monitoring activity in patients diagnosed with schizophrenia is improved by imaginary monetary incentives. Material and methods To test this hypothesis, participants were asked to memorize actions either performed or imagined during the first phase of the experiment. The second phase was to identify previous actions as performed, imagined or new, and then to express confidence using two measures of metacognition (CR or PDW scales) that were randomly allocated to participants. Results Our study showed reduced performance in the action memory task for patients with schizophrenia, although there were no group differences in confidence measures when assessing self-monitoring actions. In particular, irrespective of the diagnosis, no differences in confidence measures for correct responses were found in the case of the PDW and CR scales. We also observed that metacognitive judgements were more accurate for incorrect responses when both groups used monetary incentives to reveal their metacognition. Conclusions Our findings suggest that monetary incentives improve accuracy of metacognition among both patients and healthy controls. This accuracy-enhancing effect of monetary incentives on metacognition was possibly a result of motivational processes, including aversion to loss. The paper discusses the potential application of post-decision wagering in therapeutic metacognitive training for patients with schizophrenia.